The Manitoba Personalized Lifestyle Research (TMPLR) study protocol: a multicentre bidirectional observational cohort study with administrative health record linkage investigating the interactions between lifestyle and health in Manitoba, Canada - Navdeep Tangri; Dylan Mackay; Rebecca C Mollard; Matthew Granger; Sharon Bruce; Heather Blewett; Jared Carlberg; Todd Duhamel; Peter Eck; Patrick Faucher; Naomi C Hamm; Ehsan Khafipour; et al. (BMJ Open)
Introduction Lifestyle factors, such as diet, physical activity and sleep, are associated with the development of many chronic diseases. The objective of The Manitoba Personalized Lifestyle Research study is to understand how these lifestyle factors interact with each other and with other factors, such as an individual’s genetics and gut microbiome, to influence health.Methods An observational study of adults, with extensive phenotyping by objective health and lifestyle assessments, and retrospective assessment of early life experiences, with retrospective and prospective utilisation of secondary data from administrative health records.Study population A planned non-random convenience sample of 840 Manitobans aged 30–46 recruited from the general population, stratified by sex (equal men and women), body mass index (BMI; 60% of participants with a BMI>25 kg/m2) and geography (25% from rural areas). These stratifications were selected based on Manitoba demographics.Measurements Lifestyle factors assessed will include dietary pattern, physical activity, cardiovascular fitness, and sleep. Factors such as medical history, socioeconomic status, alcohol and tobacco consumption, cognition, stress, anxiety, and early life experiences will also be documented. A maternal survey will be performed. Body composition and bone density will be measured by dual energy X-ray absorptiometry. Blood pressure, pulse wave velocity, and augmentation index will be measured on two consecutive days. Chronic disease risk biomarkers will be measured in blood and urine samples. DNA will be extracted for genetic analysis. A faecal sample will be collected for microbiome analysis. Participants may provide their Manitoba personal health information number to link their study data with administrative health records.Ethics and dissemination Ethics approval has been obtained from the University of Manitoba Health Research Ethics Board (protocol # HS18951; 05/01/2016). Data analysis, release of results and publication of manuscripts are scheduled to start in early 2019. Additional information at www.TMPLR.ca.Trial registration number NCT03674957; Pre-results.